2008
DOI: 10.1016/j.jneuroim.2007.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Role of muscarinic receptors in the regulation of immune and inflammatory responses

Abstract: Leukocytes contain both nicotinic and muscarinic receptors, and while activation of nicotinic receptors suppresses immune/inflammatory responses, the role of muscarinic receptors in immunity is unclear. We examined the effects of a muscarinic receptor antagonist (atropine) and agonist (oxotremorine), administered chronically through miniosmotic pumps, on immune/inflammatory responses in the rat. Results show that while oxotremorine stimulated, atropine inhibited the antibody and T-cell proliferative responses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
66
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 27 publications
2
66
0
Order By: Relevance
“…Corresponding to the relatively lower effector T-cell responses in the disease-draining lymph nodes, SCPinduced DED exhibits fewer CD11b þ and T-cell infiltration in the ocular surface than CEC-induced DED, which can be due to the lower numbers of effector T-cells generated in the CLN, as well as the suppressive effect of mAChR blockade on monocytes and T-cell migration. 18 Although SCP induces weaker disease-promoting inflammatory immune responses, it generates comparable levels of clinical severity as the CEC, as demonstrated by comparable CFS scores. CFS is the recommended method of measuring ocular surface epithelial damage and the resultant barrier disruption, 21 which is the characteristic pathology of DED at the cellular level.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Corresponding to the relatively lower effector T-cell responses in the disease-draining lymph nodes, SCPinduced DED exhibits fewer CD11b þ and T-cell infiltration in the ocular surface than CEC-induced DED, which can be due to the lower numbers of effector T-cells generated in the CLN, as well as the suppressive effect of mAChR blockade on monocytes and T-cell migration. 18 Although SCP induces weaker disease-promoting inflammatory immune responses, it generates comparable levels of clinical severity as the CEC, as demonstrated by comparable CFS scores. CFS is the recommended method of measuring ocular surface epithelial damage and the resultant barrier disruption, 21 which is the characteristic pathology of DED at the cellular level.…”
Section: Discussionmentioning
confidence: 94%
“…It has been suggested that ACh regulates immune-neurohumoral crosstalk through its activity on T-cellexpressed mAChR and nicotinic ACh receptors. 15 The activation of mAChRs has been shown to enhance intracellular Ca 2þ signaling and upregulate c-fos mRNA expression, 16 increase phytohemagglutinin-induced IL-2 production, 17 enhance T-cell proliferation, 18 and decrease IFN-c synthesis. 19 Conversely, inhibition of mAChRs decreases IL-6 secretion 20 and suppresses leukocytic infiltration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Acetylcholine and its receptors have also been highlighted in vitro and in vivo to be involved in pulmonary inflammatory processes (Gosens et al, 2006). The inhibitory effects of atropine on diesel sootinduced neutrophilia (McQueen et al, 2007) and turpentine-induced leukocytic infiltration and tissue injury (Razani-Boroujerdi et al, 2008) have been demonstrated in rats. Recently, tiotropium has been reported to reduce allergen-induced airway inflammation in guinea pigs (Bos et al, 2007) and to reduce elastin degradation in patients with COPD (Ma et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These drugs primarily exhibit their bronchodilating properties but also exert anti-inflammatory effects observed in vitro (Gosens et al, 2006;Hanania and Moore, 2004) and in animal models of acute pulmonary inflammation induced by various agents including cadmium, one of the numerous components of tobacco smoke and a toxic ambient pollutant (McQueen et al, 2007;Miyamoto et al, 2004;Razani-Boroujerdi et al, 2008;Zhang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%